The Impact of Infrastructure Development on Economic Growth in West Nusa Tenggara Province - Lina Anggraini; Muhammad Alwi; Ahmad Zaenal Wafik (Future Techno-Science, 2025)
Infrastructure as one of the main supporting factors is believed to have an important role in driving economic growth, both through increasing accessibility and the quality of public services. This study aims to analyze the effect of infrastructure including roads, clean water, education, and health on economic growth in 10 districts/cities in West Nusa Tenggara Province (NTB) during the period 2019–2023. The method used is a quantitative approach with panel data analysis techniques, which combine time series data and cross-regional data (cross section). Data were obtained from the NTB Central Statistics Agency (BPS) and various supporting literature. The analysis was carried out using a panel data regression model with the help of Eviews 10 software. The selection of the best model was carried out through the Chow, Hausman, and Lagrange Multiplier Tests. Classical assumption tests and hypothesis tests (t-test and F-test) were carried out to ensure the validity of the model. The results of the study showed that clean water and education infrastructure had a positive and significant effect on economic growth, while road and health infrastructure did not show a significant effect. However, simultaneously, all infrastructure variables together have a significant effect on economic growth. The regression model used has an Adjusted R2 value of 0.978966, which indicates that 97.8% of the variation in economic growth can be explained by the infrastructure variables analyzed.